Identification of prognostic hub genes and functional role of BAIAP2L2 in prostate cancer progression: a transcriptomic and experimental study - Xiangyang Zhan; Xiangyang Zhan; Xiangyang Zhan; Xiangyang Zhan; Wenkai Wang; Jie Lian; Yichun Li; Jianyi Gu; Jianyi Gu; Jianyi Gu; Jianyi Gu; Dongdong Guo; et al. (Frontiers in Immunology)
BackgroundProstate cancer (PCa) is a prevalent malignancy in men, and understanding its molecular mechanisms is crucial for identifying therapeutic targets.MethodsTranscriptomic data from prostate tumors and matched healthy tissues were obtained from The Cancer Genome Atlas (TCGA). Differential expression analysis using the DESeq2 algorithm identified differentially expressed genes (DEGs). Cox proportional hazards regression was used to evaluate prognostic significance. Clinical validation involved comparing tumor specimens with normal tissues, focusing on BAIAP2L2, which showed significant differential expression and was further examined via immunohistochemical analysis. In vitro knockdown experiments were conducted in PC3 and DU145 cell lines to assess BAIAP2L2’s functional role through assays for migration, colony formation, and proliferation.ResultsA total of 1,449 DEGs were identified, including 775 upregulated and 674 downregulated genes. Prognostic analysis revealed 748 genes linked to clinical outcomes, with 19 hub genes identified. QPCR confirmed significant upregulation of four candidates, including BAIAP2L2, which was also elevated in malignant tissues. BAIAP2L2 knockdown significantly impaired migration, proliferation, and viability in PCa cells.ConclusionThis study highlights crucial molecular mechanisms in PCa progression, particularly the significance of BAIAP2L2 as a potential therapeutic target, warranting further investigation into additional hub genes for effective targeted strategies.